O hneve, alebo čo ponúka Heideggerova filozofia afektivity - Démuth, Andrej (Filosoﬁcký časopis)
The article presented here thematizes Heidegger’s view of affectivity, experience and passions in the context of his reading of Nietzsche’s philosophy. Following the basic plan of Heidegger’s analysis of moods (especially fear and anxiety) in Being and Time, the author attempts to show us what Heidegger’s phenomenology of affectivity would have enabled us to see in the phenomenon of anger if Heidegger had elaborated it. The author analyzes anger as a social and moral emotion through the prism of what “angry” phenomena have in common; what we perceive when we are angry; and what it is for us that anger is even about. In conclusion, anger is presented as something existential that not only uncovers existence itself, but above all the relationship of our will to phenomena that are not acceptable to us.